AB0026 A Simple Method of Removing Low Density Granulocytes from Peripheral Blood Mononuclear Cells in Autoimmune Diseases. (15th July 2016) - Zhang, S.; Shen, H.
Abstract : Background: Low density granulocytes (LDGs) can form neutrophil extracellular traps (NETs) spontaneously and excessively. When peripheral blood mononuclear cells (PBMCs) were used for studying T lymphocytes, PBMCs-contained LDGs may decrease the threshold of activating T lymphocytes by forming NETs. Objectives: This study focused on profiles of LDGs in common autoimmune diseases and method of removing LDGs from PBMCs. Methods: LDGs percentages in PBMCs from 55 dermatomyositis (DM) patients, fifteen polymyositis (PM) patients, forty-two rheumatoid arthritis (RA) patients, twenty-five SLE patients and 19 healthy controls were tested by flow cytometer. Increasing relative centrifugal force (RCF) method, PBMCs adherence method and whole blood sedimentation method were used to remove LDGs from PBMCs. PBMCs from six patients with positive T-SPOT. TB were adhered one hour and then tested for T-SPOT. TB again. Results: Compared with controls (1.28±0.73%), patients with DM (8.41±10.87%, P<0.0001), PM (8.41±10.39%, P<0.0001), RA (4.05±6.97%, P=0.0249) and SLE (7.53±11.52%, P=0.0006) showed significantly higher LDGs percentage in PBMCs. Increasing RCF in a limited range can decrease LDGs percentage for cases with high LDGs percentages, but not remarkably increase LDGs clearance rate. PBMCs adherence method can significantly remove LDGs and scarcely influence the T lymphocyte percentage in PBMCs compared to whole blood sediment method. T-SPOT. TB value significantly decreased after LDGs were removed from PBMCs by using the PBMCs adherence method. Conclusions: Similar to SLE, LDG percentages in PBMCs were significantly increased in patients with DM, PM and RA. LDGs' influences on T lymphocytes cannot be ignored in PBMCs culture. PBMCs adherence method was a simple and easy-to-use method of removing LDGs from PBMCs. Disclosure of Interest: None declared